Customer’s Perception and Service Quality on Mobile Banking Usage - Nevi Hasnita; Ana Fitria; Riza Aulia; Mira Dira Darmah (Universitas Darussalam Gontor, 2023)
The evolution of technology necessitates that banking creates an innovative and useful product for customers, such as mobile banking. This study examines the impact of perception and service quality on mobile banking usage through a quantitative methodology with a sample size of 100 respondents and the method of multiple regression analysis. Partial test results indicate that perceived benefits, perceived convenience, and service quality influence customer interest in mobile banking, however, perceived risk has no significant effect. The simultaneous test indicates that all variables have a favorable effect on client interest in mobile banking.